Empirical radiation belt models: Comparison with in situ data and implications for environment definition. Issue 9 (13th September 2017) - de Soria‐Santacruz Pich, Maria; Jun, Insoo; Evans, Robin
Abstract: The empirical AP8/AE8 model has been the de facto Earth's radiation belts engineering reference for decades. The need from the community for a better model incubated the development of AP9/AE9/SPM, which addresses several shortcomings of the old model. We provide additional validation of AP9/AE9 by comparing in situ electron and proton data from Jason‐2, Polar Orbiting Environmental Satellites (POES), and the Van Allen Probes spacecraft with the 5th, 50th, and 95th percentiles from AE9/AP9 and with the model outputs from AE8/AP8. The relatively short duration of Van Allen Probes and Jason‐2 missions means that their measurements are most certainly the result of specific climatological conditions. In low Earth orbit (LEO), the Jason‐2 proton flux is better reproduced by AP8 compared to AP9, while the POES electron data are well enveloped by AE9 5th and 95th percentiles. The shape of the South Atlantic anomaly (SAA) from Jason‐2 data is better captured by AP9 compared to AP8, while the peak SAA flux is better reproduced by AP8. The <1.5 MeV inner belt electrons from Magnetic Electron Ion Spectrometer (MagEIS) are well enveloped by AE9 5th and 95th percentiles, while AE8 overpredicts the measurements. In the outer radiation belt, MagEIS and Relativistic Electron and Proton Telescope (REPT) electrons closely follow the median estimate from AE9, while AP9 5th and 95th percentiles generally envelope REPT proton measurements in the inner belt and slot regions. While AE9/AP9 offer the flexibility to specify the environment with different confidence levels, the dose and trapped proton peak flux for POES and Jason‐2 trajectories from the AE9/AP9 50th percentile and above are larger than the estimates from the AE8/AP8 models. Key Points: We compare particle data from Jason‐2, POES, and the Van Allen Probes spacecraft with model estimates from AE9/AP9 and AE8/AP8 The shape of the SAA from Jason‐2 data is better captured by AP9 compared to AP8, while the peak SAA flux is better reproduced by AP8 Despite the unusual climatological characteristics of the Van Allen Probes era, AE9/AP9 reproduce well MagEIS and REPT observations